GAP ANALYSIS PENGEMBANGAN REMPANG ECO-CITY: ANTARA POTENSI PARIWISATA BERKELANJUTAN DAN DINAMIKA KONFLIK SOSIAL - Eva Amalia; Wahjoe Pangestoeti; Siti Arieta (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2026)
The development of Rempang Eco-City (REC) in Batam represents a strategic effort to promote sustainable tourism and regional economic growth. This study examines the gap between the planned concept and its actual implementation, particularly in tourism potential and social conflicts. Using a descriptive qualitative approach with gap analysis, data were collected through observation, interviews, documentation, and literature review, focusing on four aspects: policy and planning, social conditions, economic and tourism potential, and infrastructure and environmental readiness. The findings indicate significant gaps across all aspects. Development remains largely top-down with limited community participation, while social resistance highlights unresolved issues of rights and inclusivity. Despite strong tourism potential, progress is hindered by uncertainty and conflict, and infrastructure readiness is still inadequate. The research concludes that Rempang Eco City’s success depends on integrating social inclusion, environmental sustainability, and participatory governance, supported by community-based tourism, improved infrastructure, and inclusive policies